PEMBERDAYAAN MASYARAKAT DESA LEGUNDI DENGAN PELATIHAN PEMBUATAN PUPUK ORGANIK MENGGUNAKAN MEDIA LIMBAH BAGLOG JAMUR TIRAM - Taufikkurahman Taufikkurahman; Achmad Dhani Winarno; Ramadhan Gusti Nugraha; Rendy Christabel Benedicta Hendrawan; Stela Kesya Valentina; Salsabila Adilah Putri Endharto (KARYA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Compost is an alternative to organic fertilizer that is very environmentally friendly. Compost can be made using a lot of waste, both organic waste, household waste through the composting process. Mushroom farmers in Legundi Village, Bantaran District, Probolinggo Regency have a problem in the form of mushroom baglog waste. Mushroom baglogs are usually not used and even thrown away after the harvest. This is a good gap to use as liquid compost. This activity was carried out by a group of 117 Thematic KKN MBKM National Development University “Veterans” East Java on June 9, 2022, located in Legundi Village, Bantaran District, Probolinggo Regency. This activity was carried out by 11 (eleven) people consisting of 7 (seven) men and 4 (four) women. This activity produces ready-to-use compost for agricultural needs. The conclusions of this activity are 1) Mr. Doni's oyster mushroom cultivation which was fostered by MBKM Thematic KKN students Group 117 has understood the procedure or how to make organic compost from oyster mushroom baglog media waste, 2) education on the use of compost can be accepted by students as well as the village, and 3) the fertilizer products produced can be commercialized and have an impact on increasing the income of the oyster mushroom cultivation group of the mushroom world.